Perceptions of Interprofessional Identity Formation in Recent Doctor of Physical Therapy Graduates: A Phenomenological Study - Laura Plummer; Keshrie Naidoo (MDPI AG, 2023)
This study examined how recent Doctor of Physical Therapy graduates from a health professions graduate school with an interprofessional curriculum conceptualize their professional and interprofessional identity (i.e., dual identity). Theoretical frameworks included social identity theory, intercontact group theory, and the interprofessional socialization framework. Semi-structured interviews were conducted with 12 graduates in their first 1-2 years of practice in inpatient settings. Transcripts were analyzed using iterative and inductive phenomenological analysis to identify themes. Four themes related to professional identity emerged: from patient to physical therapist, profession exceeding expectations, connection with patient, and role affirmation through meaningful work. Six themes related to interprofessional identity emerged: valuing different mindsets, the authenticity of interprofessional education, feeling misunderstood, perceived versus true hierarchy, differing team dynamics, and being on the same page. Approaches to interprofessional education that focus on longitudinal socialization from professional education through clinical practice might best support the development of clinicians who value interprofessional collaborative practice.